A Review and Discussion of the History and Development of Defensible Space into the 21st Century - Cozens, Paul; Hillier, David (Elseview, 2012)
Oscar Newman's Defensible Space (1973) ideas have had a profound influence on both urban planning and criminology during the last 30 years or so. They underpin modern ideas of Crime Prevention Through Environmental Design (CPTED) which are increasingly being used to tackle crime by governments across the world’s developed and developing countries. This chapter discusses the background, concepts and development of Defensible Space highlighting the criticisms and increasingly popularity of these ideas. The chapter also discusses the current status and potential future directions for research in Defensible Space.